Identifikasi Batuan Gunung Api Purba di Pegunungan Selatan Yogyakarta Bagian Barat Berdasarkan Pengukuran Geolistrik - Winarti, Winarti; Hartono, Hill Gendoet (BRIN Publishing, 2015)
The study area is located between western part of Yogyakarta plains and Southern Mountains. The morphology and lithology along the Berbah-Imogiri show the existence of an ancient volcano. This is proven by outcrop of volcanic rock like lava, breccia and tuff. The aim of this study is to identify the existence of ancient volcanic rocks along Berbah-Imogiri based on geoelectrical data. The method used to perform measurements at four locations geoelectrical mapping with dipole-dipole configuration a long stretch of track for every 500 meters. Geoelectrical measurement results showed on track 1 in Source Kulon-Kalitirto, District Berbah, interpretedas volcanic rocks such as basalt lava and tuff. Tracks 2 in Pilang-Srimulyo, District Piyungan, iterpreted as volcanic rocks of scoria breccia. Tracks 3 in Ngeblak-Bawuran, District Pleret, interpreted as lava and tuff. And track 4 on Guyangan-Wonolelo, District Pleret interpreted as form of tuff and lava. Volcanic rocks are generally having a high resistivity value > 300 Ωm. The content of water or mineralization tends to reduce the resistivity value of resistant volcanic rock.